Biorefinery for heterogeneous organic waste using microbial electrochemical technology. (November 2019) - Desmond-Le Quéméner, Elie; Bridier, Arnaud; Tian, Jiang-Hao; Madigou, Céline; Bureau, Chrystelle; Qi, Yujiao; Bouchez, Théodore
Graphical abstract: Highlights: Microbial electrosynthesis in a microbial electrolysis cell is first demonstrated. A dedicated control strategy allows stable operation at 5 A/m 2 for months. Up to 4 times less power consumed compared to electrosynthesis with abiotic anode. Powering microbial electrolysis with anaerobic digestion (AD-MEC) is evaluated. Up to 22% of COD from waste may be converted to organic products in AD-MEC. Abstract: Environmental biorefineries aim to produce biofuels and platform biomolecules from organic waste. To this end, microbial electrochemical technologies theoretically allow controlled microbial electrosynthesis (MES) of organic molecules to be coupled to oxidation of waste. Here, we provide a first proof of concept and a robust operation strategy for MES in a microbial electrolysis cell (MEC) fed with biowaste hydrolysates. This strategy allowed stable operation at 5 A/m 2 for more than three months in a labscale reactor. We report a two to four-fold reduction in power consumption compared to microbial electrosynthesis with water oxidation at the anode. The bioelectrochemical characterizations of the cells were used to compute energy and matter balances for biorefinery scenarios in which anaerobic digestion (AD) provides the electricity and CO2 required for the MEC. Calculations shows that up to 22% of electrons (or COD) from waste may be converted to organic products in the AD-MEC process.